Probing ferroelectric behaviour in charge-transfer organic meta-nitroaniline - Isakov, Dmitry (2017)
Potential ferroelectricity in charge-transfer organic materials is often masked by the intrinsic conductivity. Here, we report the compelling evidence of ferroelectricity in organic pi-conjugated meta-nitroaniline (m-NA) crystals as shown by the local electromechanical measurements using the piezoresponse force microscopy (PFM) technique. m-NA is a charge-transfer molecular material with the exceptional optical non-linearity and perceptible conductivity along the crystallographic polar axis. While standard Sawyer-Tower measurements revealed an apparently lossy-dielectric hysteresis, The PFM switching spectroscopy indicated clear ferroelectric behaviour in this technologically important multifunctional material. Further study of the pyroelectric properties in m-NA crystals confirmed their high spontaneous polarization of 18 mu C/cm(2) at room temperature, comparable to the best known organic ferroelectrics. Published by AIP Publishing.